POTENSI PULAU SERANGAN SEBAGAI ATRAKSI WISATA DI KOTA DENPASAR - ratna juwita (Jurnal Ilmiah Dinamika Sosial, 2017)
ABSTRACTSerangan Island is one of the tourist destinations in Denpasar City which has a heterogeneous history and traditions. The development of this island itself has its own uniqueness that causes tourists who are already bored with the urban atmosphere but do not go too far from the city is interested to come to this island. With natural potential , cultures and manmade attractions are diverse then it is necessary promotion that will introduce Serangan Island is not only famous for turtle conservation but also has Coast and Mangrove Forest as an alternative to conduct tourism activities. The economic impacts felt by the surrounding community will also be a motivation for them to develop the island of attack to become more famousKeywords: tourism potential, pull factors of tourism, economic impact of tourism